Alcohol: basic and translational research: 15th annual Charles Lieber &1st Samuel French satellite symposium - Neuman, Manuela G.; Seitz, Helmut K.; Tuma, Pamela L.; Osna, Natalia A.; Casey, Carol A.; Kharbanda, Kusum K.; Cohen, Lawrence B.; Malnick, Steve D. H.; Adhikari, Raghabendra; Mitra, Ramyajit; Dagur, Raghubendra Singh; Ganesan, Murali; et al. (Experimental and molecular pathology, 2022)
The present review is based on the research presented at the symposium dedicated to the legacy of the two scientists that made important discoveries in the field of alcohol-induced liver damage: Professors C.S. Lieber and S.W. French. The invited speakers described pharmacological, toxicological and patho-physiological effects of alcohol misuse. Moreover, genetic biomarkers determining adverse drug reactions due to interactions between therapeutics used for chronic or infectious diseases and alcohol exposure were discussed. The researchers presented their work in areas of alcohol-induced impairment in lipid protein trafficking and endocytosis, as well as the role of lipids in the development of fatty liver. The researchers showed that alcohol leads to covalent modifications that promote hepatic dysfunction and injury. We concluded that using new advanced techniques and research ideas leads to important discoveries in science.